Attractiveness of the Russian Regional Space as a Living Environment: Aspect of the Migrants’ Behavioural Rationality - Petrov, Mikhail Borisovich; Kurushina, Elena Viktorovna; Druzhinina, Irina Vasilevna (Economy of Regions, 2019)
This study focuses on the rationality of the migrants’ behaviour. We hypothesise that the migration growth rate depends on the territory attractiveness for living. The rational behaviour is defined as the direct dependence of the migrations on the characteristics of the territory attractiveness. The irrational behaviour means that the reverse dependence is present. The direct dependence is recognised if the level of the migrants’ positive reactions to the factors of the territory attractiveness is no less than 30 % from the maximum. 83 subjects of the Russian Federation were clustered based on 12 objective characteristics of the life’s quality. We distinguished the largest Middle Cluster, which includes 56 regions. Further we transformed the panel data for the period from 2005 to 2015 into the array of the coefficients of correlations between the characteristics of the territory attractiveness and the migration growth rates in the regions. Using these characteristics, the regions were clustered again. The regional types of the Middle cluster with the rational and irrational behaviours include 22 regions each. The level of the migrants’ positive reactions to the factors of the territory attractiveness is 44.1 % for the first (rational) regional type and 42.5 % for the second (irrational) type. The regional type with the indifferent behaviour includes 12 regions. The level of the migrants’ reactions to the characteristics of these territory attractiveness is just 5.8 %. Based on the regression models of the migration coefficient for each cluster type, we have provided recommendations for managing the migration flows using the differential approach.